Switching Metal Ion Coordination and DNA Recognition in a Tandem CCHHC-type Zinc Finger Peptide - Besold, Angelique N. (2013)
[Image: see text] Neural Zinc Finger Factor-1 (NZF-1) and Myelin Transcription Factor 1 (MyT1) are two homologous nonclassical zinc finger (ZF) proteins that are involved in the development of the central nervous system (CNS). Both NZF-1 and MyT1 contain multiple ZF domains, each of which contains an absolutely conserved Cys(2)His(2)Cys motif. All three cysteines and the second histidine have been shown to coordinate Zn(II); however, the role of the first histidine remains unresolved. Using a functional form of NZF-1 that contains two ZF domains (NZF-1-F2F3), mutant proteins in which each histidine was sequentially mutated to a phenylalanine were prepared to determine the role(s) of the histidine residues in DNA recognition. When the first histidine is mutated, the protein binds Zn(II) in an analogous manner to the native protein. Surprisingly, this mutant does not bind to target DNA (β-RAR), suggesting that the noncoordinating histidine is critical for sequence selective DNA recognition. The first histidine will coordinate Zn(II) when the second histidine is mutated; however, the overall fold of the protein is perturbed leading to abrogation of DNA binding. NZF-1-F2F3 selectively binds to a specific DNA target sequence (from β-RAR) with high affinity (nM); while its homologue MyT1 (MyT1-F2F3), which is 92% identical to NZF-1-F2F3, binds to this same DNA sequence nonspecifically. A single, nonconserved amino acid residue in NZF-1-F2F3 is shown to be responsible for this high affinity DNA binding to β-RAR. When this residue (arginine) is engineered into the MyT1-F2F3 sequence, the affinity for β-RAR DNA increases.